Multiple and bilateral kidney tumors with clear cells of three different histotypes: A case report with clinicopathologic and molecular study. Issue 7 (7th April 2016) - Raspollini, Maria Rosaria; Castiglione, Francesca; Martignoni, Guido; Lapini, Alberto; Cheng, Liang; Montironi, Rodolfo; Lopez‐Beltran, Antonio
Abstract : We describe a rare multicentric neoplastic disease arising bilteraly in the kidney. The patient was a 70‐year‐old man, who, during a period of 3 years, was treated for five independent tumors of three histotypes (three multilocular cystic clear cell renal cell neoplasms of low malignant potential, one clear cell renal cell carcinoma, and one clear cell papillary renal cell carcinoma, respectively). Pathologic diagnosis of the reported tumors was confirmed by immunohistochemical analyses, including CD10, CA IX, CK7, AMACR/RACEMASE, and 34 beta E12. Molecular detection of KRAS, BRAF, NRAS, PIK3CA, ALK, ERBB2, DDR2, MAP2K1, RET, and EGFR gene mutational analysis was also performed in all tumors.